Correlation of degenerative meniscus injury with lower limb alignment: a clinical report of 90 cases - ZHANG Huilin; XIE Feng; XU Mingdeng (陆军军医大学学报, 2024)
Objective To compare the differences in lower limb force line between degenerative medial meniscus injuries and lateral meniscus injuries and investigate their correlation. Methods A total of 90 patients who underwent arthroscopic treatment for meniscal injuries between March 2019 and March 2022 were enrolled in the study. They were 45 males and 45 females, at a median age of 52 years (ranging from 40 to 59 years). Of these patients, 47 had medial meniscus injuries, while 43 had lateral meniscus injuries. The hip-knee-ankle (HKA) angle was measured on full-length films, and the differences were compared between the 2 groups. Results There were no significant differences in terms of gender, age, lower limb laterality, body mass index, site of injury, and type of injury between the medial meniscus injury group and the lateral meniscus injury group. Statistical difference was observed in the mean HKA angle, with a value of (177.20±2.46)° in the medial meniscus injury group and of (181.05±3.13)° in the lateral meniscus injury group (P<0.01). Conclusion There is a significant difference in HKA angle between medial meniscus injury group and the lateral meniscus injury group. A correlation is found between lower limb alignment and degenerative meniscus injury.